The Contribution of Changing Energy and Import Prices to Changing Average Labor Productivity: A Profit Formulation for Canada - Mountain, Dean C. (Quarterly Journal of Economics, 1985)
In the 1970s there has been a noticeable labor productivity slowdown in Canada. In addition to contributions of such traditional variables as changes in capital intensity and quality of labor, this study quantifies contributions of higher energy and changing import prices to productivity changes. A Taylor series approximation to a restricted profit function representing the Canadian economy helps reveal that rising energy prices have reduced labor productivity by 0.53 percent per year after 1970 and that the underlying modified rates of technical progress in the 1960s and 1970s, having netted out price of energy—and import—effects, are not dissimilar.